Please look at me? Connecting self esteem and online self-presentation among teenagers on social media instagram - Arnani Ni Putu Rizky; Nindhita Vidya (E3S Web of Conferences, 2024)
The evolving landscape of social media in the present day contributes to the revitalization of social relationship. The use of social media platforms continues to integrate into adolescents of life and essential for identity development. Adolescentes have a need for self-existence, and social media serves as a medium to fulfil this need within their friendship circles. This research aims to seek the relationship between self-esteem and online self-representation among adolescents who use instagram. This study employed quantitative approach with correlation method. The data were collected using two instruments: a self-esteem scale and online self-representation scale. The respondents of this research were 154 adolescents in MAN Bangkalan. The analysis was conducted using simple regression. The results showed that the self-esteem had a significant effect on online self-representation, resulting in meaningful contribution of 6%.